Al-Munasabah: Pengertian, Macam-Macam, Dan Manfaat Mempelajarinya - Faizatul Walidah Arrosikhoh; Hakmi Hidayat; Ulil Inayati; Jafar Maulana (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
Al-Munasabah is the relationship between verses and surahs in the Qur'an, which has an important role in understanding and interpreting the Qur'an. The arrangement of surahs in the Qur'an is not random but structured. This study aims to improve one's understanding of the Qur'an by knowing the definitions, types, and benefits of studying al-Munasabah. The qualitative research method used in this study involves a literature review of several scientific works and books that discuss coherence between verses and surahs. Munasabah can help in interpreting Qur'anic verses as well as the relationship between one verse and another.